Association between dietary acid load and the risk of hypertension among adults from South China: result from nutrition and health survey (2015-2017) - Shao-wei Chen; Gui-yuan Ji; Qi Jiang; Ping Wang; Rui Huang; Wen-jun Ma; Zi-hui Chen; Jie-wen Peng (BMC, 2019)
Abstract Background Higher dietary acid load (DAL) was considered to be associated with an elevated risk of hypertension, while related data from mainland China remains scarce and incomplete. We aim to evaluate the association between DAL and the risk of hypertension among adults from South China. Methods We conducted a nutrition and health survey in Guangdong Province located in southern China from 2015 to 2017. A four-stage probability sampling method was utilized to select representative samples of citizens aged ≥18 years old. DAL was assessed by potential renal acid load (PRAL) and net endogenous acid production (NEAP). Participants were divided to 4 groups (Q1-Q4) according to the quartile points of PRAL or NEAP distributions. Generalized linear mixed effects models were applied to evaluate the association between DAL and the risk of hypertension. Results A total of 3501 individuals were eligible for this study and 45.9% was male participants. Hypertension rate was 30.7%. A higher PRAL was associated with higher prevalence rate of hypertension among the male (P-trend = 0.03). OR for Q2 was 1.34 (95%CI, 0.94-1.91), Q3 was 1.53 (95%CI = 1.08, 2.16) and Q4 was 1.51 (95%CI, 1.08-2.16) among the male. However, as for total participants, the female, the participants with ≤55 years or participants with > 55 years, the associations were lack of significance. With respect to association between NEAP and hypertension, non-significant results were identified. Conclusions The current study indicated male hypertension was associated with higher PRAL, while given to this study was cross-sectional design, further studies are warranted to verify the association.